IMPLEMENTING CUSTOMER-CENTRIC APPROACHES IN THE RESTAURANT INDUSTRY: ANALYTICS, MOTIVATION, EFFICIENCY - Stebliuk, N. F.; Nebaba, N. O.; RazinkovaМ. Yu.; Hryshchenko, S. V. (Systems and Technologies, 2025)
The article explores current trends in the development of the restaurant business, which are associated with the need to respond promptly to changes in market conditions and increase the level of consumer expectations, and actualize the implementation of customer-oriented approaches in the service system of business models of establishments. The impact of a customer-oriented approach, staff motivation and key performance indicators (KPI) on the quality of service and the effectiveness of the activities of restaurant business establishments is determined. Key performance indicators are determined, which allow not only to determine the level of customer satisfaction, but also to identify weaknesses in the service process, and therefore, to improve business processes based on the obtained analytics. Specialized training programs are proposed, which are aimed at increasing the efficiency of personnel management in the restaurant business and improving the quality of customer service. It has been established that the focus on service quality, personalized interaction with consumers and the creation of a comfortable communication environment contributes to an increase in customer satisfaction, reducing their churn and stimulating repeated consumption. It has been determined that systematic monitoring of key performance indicators allows for timely identification of problem areas, optimization of business processes and effective use of marketing resources. The feasibility of implementing specialized motivational programs that positively affect staff productivity, reduce staff turnover and create a favorable internal climate has been substantiated. The practical significance of the results obtained lies in the possibility of their direct application in the activities of restaurant business establishments to improve the customer service system based on a customer-oriented approach. The results obtained can also be used to increase the economic efficiency and sustainability of restaurant business establishments in conditions of high competition. Prospects for further research are the development of digital KPI monitoring tools, the study of the impact of staff emotional intelligence on customer experience, as well as a comparative analysis of the effectiveness of customer-oriented strategies in different formats of restaurant business establishments.